Pengaruh Terpaan Iklan Sampo Clear dan Kelompok Referensi terhadap Keputusan Pembelian Sampo Clear - Florensia Sonia Haniswari; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Clear is a shampoo brand that focuses on the problem of dandruff that promotes its products through advertising on various media, but sales of Clear shampoo have always declined over the past five years with an average decline of 1.06% annually. This study aims to analyze the effect of Sampo Clear advertising exposure and reference groups on the decision to purchase Clear Shampoo. The theory used is Advertising Exposure Theory to support the influence of Clear Shampoo exposure and Social Influence Theory to support the influence of reference groups on Clear Shampoo purchasing decisions. This research is a type of descriptive research with non probability incidental sampling technique. The study was conducted on 100 respondents aged 18-35 years who lived in Semarang, had seen Sampo Clear advertisements, knew about Sampo Clear products, and had considered buying Clear Shampoo. Data analysis was carried out by a simple linear regression test using SPSSS which was done twice to test each hypothesis. The results of the study show that consumers have a fairly good understanding of the contents of Clear Shampoo ads. However, from the hypothesis test, the results show that the exposure of Clear Shampoo (X1) does not have a significant effect on the purchase decision of Clear Shampoo (Y), which is indicated by a significance value> 0.05, which is 0.654, so the first hypothesis is not accepted. While the reference group (X2) has a very significant influence on the decision to purchase Clear Shampoo (Y) because the test results show a positive correlation and a significance number of 0,000 so that the second hypothesis is accepted. So the researchers suggested Clear to use a more creative promotion strategy to encourage people to talk about Sampo Clear, which then directed them to purchase, but did not eliminate the advertisement because the reminding function and the informing went well.